Safari Qira’ah wa Ta’lim: Peningkatan Literasi Al-Qur’an di Desa Glingseran Kecamatan Wringin Kabupaten Bondowoso - Abd. Basid; Ahmad Maulidin; Deki Febrian; Kusyairi Kusyairi (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2026)
This program aims to enhance accurate Qur’anic reading skills, reinforce religious understanding, and foster community participation in sustainable Qur’anic education. The community service methodology employed a structured approach, including needs assessment, program planning, instructional implementation through lectures, discussions, and hands-on practice, as well as supporting activities, monitoring, and evaluation based on observations, competency tests, and participant feedback. The findings indicate a significant improvement in participants’ ability to read the Qur’an with proper tajwid, increasing from approximately 50% prior to the program to 85% after its implementation, along with improved basic comprehension of Qur’anic content among 75% of participants. The program also strengthened the roles of Qur’anic teachers, religious leaders, parents, and the broader community in creating a participatory Qur’anic learning ecosystem. From a policy perspective, these findings highlight the need for support from local governments, religious institutions, and relevant stakeholders in developing community-based Qur’anic literacy programs, enhancing the capacity of Qur’anic instructors, providing adequate learning facilities, and establishing independent learning groups as a strategy for sustaining religious education at the village level.